Publications, Series - Boyd, Louise Arner, 1887-1972; American Geographical Society of New York (1934)
General correspondence about the details concerning the publication of Louise Boyd's book "The Fiord Region of East Greenland" (1935). Also includes a echo sounding report and a discussion about the photographs.